IDDF2018-ABS-0180 Cardiac tamponade in acute necrotising pancreatitis. (June 2018) - Goh, Lu Hern; Tan, Chee Keat; Chong, Bryan; Loi, Jolene; Thong, Christopher
Abstract : Background: This case report highlights cardiac tamponade as a potentially significant complication of severe acute pancreatitis. This patient was admitted to the Ng Teng Fong general hospital emergency department. He was subsequently admitted to the Intensive Care Unit (ICU) in the same hospital. Methods: A 58-year-old Chinese male presented with a 1 day history of the central chest and epigastric pain radiating to the back, worse after meals and associated with one episode of vomiting without fever. He has past medical history of biliary colic, chronic hepatitis B, alcoholic fatty liver disease, psoriasis and hypertension. Patient's alcohol use is estimated to be 25 units a day for the past 30 years but claims to have stopped alcohol use 6 months prior to admission. He was diagnosed with severe acute gallstone pancreatitis with a Glasgow-Imrie criteria of 3. He was admitted to the ICU for haemodynamic instability and acute respiratory distress syndrome (ARDS). The patient developed new-onset atrial fibrillation, persistent hypotension despite fluid resuscitation and increasing dependence on high inotropic support. Results: A CT scan revealed severe necrotising pancreatitis with a significant peripancreatic fluid collection (figure 1). CT abdomen incidentally discovered an accumulation of pericardial fluid. Bedside echocardiography confirmed the presence of a large pericardial effusion consistent with cardiac tamponade. A repeat CT abdomen showed rapidly accumulating pericardial fluid (IDDF2018-ABS-0180 Figure 2. Ct of the abdomen and pelvis on day 32 pericardial effusion white arrow). An emergency pericardiocentesis was performed, and a pericardial drain was inserted. 80=of haemoserous pericardial fluid was drained over a period of 2 days. Patient's haemodynamic status improved significantly after drainage of pericardial fluid. The patient was weaned off noradrenaline inotropic support. Conclusions: Cardiac tamponade is one of the rare but clinically significant complications of severe acute pancreatitis and should be treated with a high index of suspicion in cases of acute pancreatitis with hypotension. As a rapidly accumulating pericardial effusion is relatively easy to manage before it develops the above complications, it is important to consider doing serial echocardiograms for patients who have pericardial effusions in acute pancreatitis to ensure there is no rapid accumulation which might further complicate treatment.